Korelasi Pemahaman Remaja Tentang Kegawatdaruratan Narkoba Dengan Kesiapan Menyatakan Sikap Menolak Menggunakan Narkoba - Fathimi, Fathimi; Sasmita, Yenni; Orisinal, Orisinal; Yasni, Hilma; Rasima, Rasima; Devi, Desriati (Journal Keperawatan, 2024)
Background: The threat of drugs continues to haunt people's lives, causing parents to worry about the safety and security of their children's future, including causing widespread negative impacts both physically, psychologically, economically, socially, culturally and etc. If drug abuse is not properly anticipated, it will damage and threaten the sustainability of Indonesia's young generation. Teenagers are a group of people who are at risk of drug abuse and are often synonymous with searching for identity, thus encouraging teenagers to want to try something new, including trying to take drugs. Purpose: To find out whether there is a relationship between teenagers' understanding of the emergency of drugs and their readiness to express an attitude of rejecting drug use. Method: The research method used is observational with a cross-sectional study design, where measurements are only carried out once between the independent and dependent variables. The number of samples used was 37 respondents from Madrasah Tsanawiyah Negri 3 Tapaktuan, South Aceh. Results: There is a significant relationship between teenagers' understanding (P=0.001) and teenagers' daily interactions with their readiness to express their attitude of rejecting drugs (P=0.000) where the p value is <0.05.  Conclusion: There is a relationship between adolescent understanding and adolescent interactions with readiness to reject drugs.